The Limits of Rational Knowledge of God According to Joseph Ratzinger - Borto, Paweł (Verbum Vitae, 2023)
Joseph Ratzinger’s theological thought is distinguished by the conviction that the Christian knowledge of God is closely associated with the concept of the Logos. Therefore, in his reflection, Joseph Ratzinger is a theologian who seeks to render the mystery of God in positive terms. Yet, it would be a mistake to leave this statement without adding that in the rational knowledge of God, theology should at the same time confront what constitutes the limit of rational knowledge. The aim of this article is therefore to provide an overview of how Joseph Ratzinger pointed to the limits of the rational knowledge of God. A two-step method was adopted to achieve this goal. With reference to the synthetic approach, it first accounts for the place that the question of the rational knowledge of God takes in J. Ratzinger’s theological reflection; then it points out how, according to the German theologian, we should understand the apophatic dimension of all theological knowledge; namely, that God, being the infinite Love, can only be known in aspects, and only in the attitude of surrender. In the next step, the most significant aspects of Joseph Ratzinger’s theological reflection on theological knowledge were selected. The analysis of representative texts demonstrates how the German theologian understands limits in the rational knowledge of God. Thus, the understanding of rationality closed to the knowledge of God was presented first, along with the requirements that reason has to meet in order to open itself to the knowledge of God. Then it was demonstrated which of the most important areas of J. Ratzinger’s theological reflection refer to the limits of rational knowledge, and how they do it. The article concerns the limits of knowledge determined by the Revelation, the mystery of God, and the personal centre of Revelation – Christ, as well as the ecclesiastical nature of the creed.